Unraveling factors affecting consumers’ liking of novel Uruguayan mandarins - Lado, Joanna; Moltini, Ana Inés; Pintos, Pedro; Luque, Eleana; Goncalvez, Lucía; Rivas, Fernando; Alcaire, Florencia; Ares, Gastón (Agrociencia Uruguay, 2021)
Mandarin cultivars show a great diversity on fruit-quality and sensory characteristics, together with an extended harvest season. Citrus breeding is focused on exploiting season niches for higher prices as well as nutritional and sensory aspects, among others. In this context, the sensory characterization of new hybrids and the identification of key characteristics of consumers´ liking provide valuable information towards breeding efforts and marketing strategies. Previous works showed that sensory characteristics, and specially flavor, play a key role in consumer acceptance of mandarins. Two studies were carried out during mandarin harvest season (mid and late) applying “check all that apply” (CATA) questions with at least 100 consumers. Overall liking scores of the most liked hybrids and cultivars ranged between 6.5 to 7.7 in the 9-point hedonic scale, evidencing a positive hedonic reaction. Local hybrids showed similar or higher values than the reference cultivars Tango, Gold Nugget, Murcott and Ortanique. Results showed that orange color, regular shape, smoothness, sweetness, juiciness, intense and typical flavor are the key drivers of consumer's liking of mandarins, and that external appearance is not a good predictor of mandarin tasting experience. Hybrids F3P8, F5P8 and F2P3 were described using terms related to positive sensory characteristics and received liking scores similar or higher to reference cultivars such as Tango, stressing the importance of sensory and consumer science as an integral part of breeding strategies.